CUL4-Based Ubiquitin Ligases in Chromatin Regulation: An Evolutionary Perspective - Makiko Nakagawa; Tadashi Nakagawa (Cells)
Ubiquitylation is a post-translational modification that modulates protein function and stability. It is orchestrated by the concerted action of three types of enzymes, with substrate specificity governed by ubiquitin ligases (E3s), which may exist as single proteins or as part of multi-protein complexes. Although Cullin (CUL) proteins lack intrinsic enzymatic activity, they participate in the formation of active ubiquitin ligase complexes, known as Cullin-Ring ubiquitin Ligases (CRLs), through their association with ROC1 or ROC2, along with substrate adaptor and receptor proteins. Mammalian genomes encode several CUL proteins (CUL1–9), each contributing to distinct CRLs. Among these CUL proteins, CUL1, CUL3, and CUL4 are believed to be the most ancient and evolutionarily conserved from yeast to mammals, with CUL4 uniquely duplicated in vertebrates. Genetic evidence strongly implicates CUL4-based ubiquitin ligases (CRL4s) in chromatin regulation across various species and suggests that, in vertebrates, CRL4s have also acquired a cytosolic role, which is facilitated by a cytosol-localizing paralog of CUL4. Substrates identified through biochemical studies have elucidated the molecular mechanisms by which CRL4s regulate chromatin and cytosolic processes. The substantial body of knowledge on CUL4 biology amassed over the past two decades provides a unique opportunity to explore the functional evolution of CRL4. In this review, we synthesize the available structural, genetic, and biochemical data on CRL4 from various model organisms and discuss the conserved and novel functions of CRL4s.